Ionophore Antibiotics as Cancer Stem Cell-Selective Drugs: Open Questions. (2nd August 2016) - Boesch, Maximilian; Sopper, Sieghart; Wolf, Dominik
Abstract : Ionophore antibiotics are promising compounds with potent anticancer and anti-cancer stem cell (anti-CSC) activity. However, resistance mediated by drug transporters potentially confines their use to CSC populations that do not exhibit appreciable drug efflux capacity. Further research is required to delineate which CSC subsets are likely to be susceptible to ionophore antibiotic cytotoxicity.